2011
DOI: 10.1253/circj.cj-10-1050
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of Ca2+ Waves in Monocrotaline-Induced Right Ventricular Hypertrophy in the Rat

Abstract: Circulation Journal Official Journal of the Japanese Circulation Society http://www. j-circ.or.jp rrhythmias are likely to occur in diseased hearts, 1-3 and delayed afterdepolarizations (DADs) play an important role 4 in their occurrence, associated with catecholamine excess, 5 heart failure, 6 and mutations of the ryanodine receptor or calsequestrin. 7 Such diseased hearts not only exhibit an increase in diastolic intracellular Ca 2+ ([Ca 2+ ]i), 8 which causes spontaneous Ca 2+ release from the sarcoplasmic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…In addition to SERCA2a, Kogler et al, found that other calcium-handling proteins such as phospholamban and ryanodine receptor were also downregulated only in the RV, but not in the LV of MCT-treated rats 26 . In a recent study Miura et al suggested that an increase in diastolic [Ca 2+ ]i and an increase in Ca 2+ sensitivity of the sarcoplasmic reticulum Ca 2+ release channel accelerate Ca 2+ waves in ventricular hypertrophy, thereby causing arrhythmogenesis in the RV of MCT-induced PH 33 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to SERCA2a, Kogler et al, found that other calcium-handling proteins such as phospholamban and ryanodine receptor were also downregulated only in the RV, but not in the LV of MCT-treated rats 26 . In a recent study Miura et al suggested that an increase in diastolic [Ca 2+ ]i and an increase in Ca 2+ sensitivity of the sarcoplasmic reticulum Ca 2+ release channel accelerate Ca 2+ waves in ventricular hypertrophy, thereby causing arrhythmogenesis in the RV of MCT-induced PH 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Benoist and collaborators (4) have described a proarrhytmogenic substrate in the hearts of MCTtreated animals. Whether MCT-induced myocarditis or arrhythmias (4,42) are the cause of death in rats, which can tolerate higher levels of RV afterload, remains undetermined but should be considered.…”
Section: Mct-induced Myocarditismentioning
confidence: 99%
“…; Miura et al . ; Lookin et al . ), and (iv) decreased expression of the sarcoplasmic reticulum Ca 2+ ‐ATPase (Kogler et al .…”
Section: Introductionmentioning
confidence: 99%